Haemodynamic effects of glucagon. Issue 3 (May 1970) - Murtagh, J. G.; Binnion, P. F.; Lal, S.; Hutchison, K. J.; Fletcher, E.
Abstract : The central and peripheral vascular haemodynamic effects of glucagon were studied in 29 patients. With a single dose method of 2 or 5 mg. glucagon intravenously the inotropic action of the drug produced immediate increased myocardial contractility with significant increase in cardiac output and enhanced cardiac performance, and lowering of pulmonary arterial pressure and pulmonary vascular resistance. No primary peripheral vascular effect was evident, and the increased systemic pressure and lowered systemic resistance appear to be secondary to the central action of the drug. With the dosage used there were no undesirable side-effects apart from a feeling of slight nausea. Though the haemodynamic effects are abrupt, reaching their maximum values in the first 10 minutes after injection, they tend to be dissipated within half an hour, presumably due to the very rapid destruction of the drug. Repeated booster doses rather than continuous infusion may be the method of choice to maintain an increased cardiac output. The positive chronotropic action of the drug may cause transient palpitations. Glucagon increased the cardiac output in the acute phase of myocardial infarction by 42 per cent. The haemodynamic effects in chronic rheumatic heart disease are more varied, and it may increase left atrial pressure in mitral stenosis, which is undesirable. Hyperglycaemia results from liver glycogenolysis but blood sugar levels rarely exceeded 200 mg./100 ml. These results warrant further study of the value of glucagon as a positive inotropic agent in low output heart failure, especially in acute myocardial infarction with cardiogenic shock, or after cardiac surgery, or in unrelieved chronic congestive heart failure.